Adherence to Canadian 24-Hour Movement Guidelines among infants and associations with development: a longitudinal study - Valerie Carson; Zhiguang Zhang; Madison Predy; Lesley Pritchard; Kylie D. Hesketh (BMC, 2022)
Abstract Background To examine: 1) longitudinal adherence to the Canadian 24-Hour Movement Guidelines in a sample of infants and 2) associations between adherence to the guidelines over time and development. Methods Participants were 250 parent-infant dyads from the Early Movers project in Edmonton, Alberta. At 2, 4, and 6 months of age, physical activity, sedentary behaviour, sleep, and development were measured with a parental questionnaire that included items from the Ages & Stages Questionnaire (ASQ-3). Parents also reported the dates six major gross motor milestones were acquired during the first 18 months of life according to World Health Organization criteria. In a sub-sample (n = 93), movement behaviours were also measured with a time-use diary at 2, 4, and 6 months and gross motor development was measured by a physiotherapist using the Alberta Infant Motor Scale (AIMS) at 6 months. Guideline adherence was defined as: 1) ≥ 30 min/day of tummy time, 2) no screen time, some reading time, no restrained bouts > 1 h (time-use diary only), and 3) 14-17 h (2 months) or 12-16 h (4 and 6 months) of sleep per 24-h period. Generalized estimating equations were conducted as well as linear mixed models and linear regression models that adjusted for demographic characteristics. Results Few infants met the guidelines at all time-points (questionnaire: 2%; time-use diary: 0%). Infants that met a recommendation at 2 months, compared to those that did not, were 1.8-8.2 times more likely to meet that recommendation at subsequent time-points. Meeting more recommendations across time-points, according to both measures, was associated with a higher mean ASQ-3 gross motor score. Each additional time-point of tummy time recommendation adherence (questionnaire-measured) was associated with a 5-11-day earlier acquisition of independent sitting, crawling, and independent standing milestones. In the sub-sample, each additional time-point of guideline adherence was associated with a 16% higher AIMS score at 6 months. Conclusions Guideline adherence was low across the first 6 months of infancy. Overall, meeting more recommendations over this period appeared important for gross motor development. Parents and caregivers should be targeted as early as possible with guideline dissemination and activation strategies to promote healthy infant development.